PERBEDAAN PERSEPSI MAHASISWA SENIOR DAN JUNIOR MENGENAI PROFESI AKUNTAN PADA PROGRAM S1 DI UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA - HWI HWOA, ANG (: 2303-1719)
Accounting profession is work that has to be done in a professional and great responsibility towards the public,so that every student who will pursue this work should have the right attitudes and perceptions of the accounting profession. Therefore, when students still in the university they need to be taught to has a positive perception of accounting profession. This research used comparative with hypothesis testing aims to provide empirical evidence on differences in perceptions between senior and junior students of the accounting profession. The samples consist of senior students who have passed all internal and external courses (class of 2007 and 2008) and junior students who have passed the semester 1 (class of 2009 and 2010). The numbers of samples used by proportionate random sampling are 72 samples from senior students and 102 samples from junior students. The tool used is questionaire that contain list of statements. The results showed that there was no difference in perception between senior and junior students of the accounting profession in the bachelor of accounting at Widya Mandala Catholic University Surabaya.